Knowledge of nephrology nurses on evidence based guidelines for prevention of haemodialysis catheter related infections - Ntlhokoe, Mphanye Joseph (My University, 2016)
The purpose of the study was to determine knowledge of nephrology nurses’ on evidence based guidelines for the prevention of haemodialysis catheter related infections. The study was done in 5 haemodialysis units from two university-affiliated, public sector and tertiary level hospitals in Gauteng which are: “Baragwanath Hospital and Charlotte Maxeke Academic Hospital”. Face and content validation of the research instrument “Evaluation questionnaire concerning nurses’ knowledge of interventions for prevention of haemodialysis catheterrelated bloodstream infections” was done by a panel of experts to ensure applicability of the instrument to the South African context. Prior to commencement of the study, ethical clearance and permission to conduct the study was obtained from the relevant authorities and the university committee. A non-experimental, descriptive, prospective study design was utilised in order to meet the objectives of the study. Descriptive and comparative statistics were used to analyse the data which was done in consultation with a statistician. Knowledge was reorganised as poor (0-50%), average (50-70%) and good (71% and above). Overall, participants performed well in the second part of the questionnaire where their knowledge was tested regarding evidence based guidelines in prevention of vascular access infection; the majority 72.50% (n=58) scored more than 71%, indicating they have knowledge of evidence based guidelines on prevention of vascular access infection, 20% of participants scored between 51 and 70%, whilst only 2% scored below 50%. A positive correlation (with moderate strength) between age and experience (r=0.563) was established indicating that as age increases the experience will also increase moderately. A slight negative correlation, which was very weak (null correlation) was also established between years of experience and performance as most respondents were above and below the regression line. Therefore years of experience has no influence over performance.
A research report submitted to the Faculty of Health Sciences, University of the Witwatersrand, Johannesburg in partial fulfilment of the requirements for the degree of Master of Science in Nursing Johannesburg, 2016
Keywords: Nephrology; Haemodialysis; Catheter; Catheter-Related Infections; Hemodialysis Units, Hospital